2020
DOI: 10.1038/s41598-020-70648-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of Xenotime-type rare earth phosphate REPO4, (RE = Lu, Yb, Er, Y and Sc) for potential environmental barrier coating applications

Abstract: & fan Wan the mechanical and thermophysical properties of Xenotime-type Repo 4 (Re = Lu, Yb, er, Y and Sc) have been theoretically and experimentally investigated for a potential environmental barrier coating (eBc) topcoat application. the results show that the current studied Repo 4 exhibits a quasiductile property, suggesting a potential long life expectancy of its made coatings. further, from the study of underlying parameters governing thermophysical properties of a ceramic, low thermal expansion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…It is also observed that the addition of NiFe 2 O 4 @AC composite to UiO‐66(Zr) MOF does not destroy the diffraction pattern compared with bare UiO‐66(Zr). According to Bragger's law, The deviation of peaks of NiFe 2 O 4 @AC/UiO‐66(Zr)‐ 2 than the pristine NiFe 2 O 4 @AC and UiO‐66(Zr) to lower angle is attributed to the incorporation of NiFe 2 O 4 @AC with UiO‐66(Zr) MOF with increasing size of the prepared material [30] . Also, the MOFs can adsorb the moisture from the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that the addition of NiFe 2 O 4 @AC composite to UiO‐66(Zr) MOF does not destroy the diffraction pattern compared with bare UiO‐66(Zr). According to Bragger's law, The deviation of peaks of NiFe 2 O 4 @AC/UiO‐66(Zr)‐ 2 than the pristine NiFe 2 O 4 @AC and UiO‐66(Zr) to lower angle is attributed to the incorporation of NiFe 2 O 4 @AC with UiO‐66(Zr) MOF with increasing size of the prepared material [30] . Also, the MOFs can adsorb the moisture from the atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alumina tubes at temperatures higher than 1500 • C produces Al(OH) 3 and causes alumina pollution, which makes it difficult to quantitatively formulate the corrosion process. Han et al 96 found that the alumina tube reacted with water vapor to form Al(OH) 3 , and then it reacted with REPO 4 (RE = Lu, Yb, Y, and Sc) ceramics to form Al 5 RE 3 O 12 . Similarly, Opila 97 found that the oxidation rate of SiC in water vapor was an order of magnitude higher than that in the molten quartz tube furnace.…”
Section: Gas Flow Velocitymentioning
confidence: 99%
“…Without any protection, SiC f /SiC composites cannot be applied in gas turbines. Environmental barrier coatings (EBCs) are conventionally employed to physically isolate SiC f /SiC composites from direct contact with corrosive combustion steam 10–12 . Normally, they are composed of at least two layers, namely, the bond coat and topcoat, respectively.…”
Section: Current (A) Ar (Slm) H2 (Slm) Distance (Mm) Power (Kw)mentioning
confidence: 99%